Caregiver Burden in Alzheimer's Disease: Differential Associations in Adult-Child and Spousal Caregivers in the GERAS Observational Study - Catherine Reed; Mark Belger; Grazia Dell'Agnello; Anders Wimo; Josep Maria Argimon; Giuseppe Bruno; Richard Dodel; Josep Maria Haro; Roy W. Jones; Bruno Vellas (Dementia and Geriatric Cognitive Disorders Extra, 2014)
Background/Aims: To examine factors influencing the caregiver burden in adult-child and spousal caregivers of community-dwelling patients with Alzheimer's disease (AD). Methods: Baseline data from the 18-month, prospective, observational GERAS study of 1,497 patients with AD in France, Germany, and the UK were used. Analyses were performed on two groups of caregivers: spouses (n = 985) and adult children (n = 405). General linear models estimated patient and caregiver factors associated with subjective caregiver burden assessed using the Zarit Burden Interview. Results: The caregiver burden increased with AD severity. Adult-child caregivers experienced a higher burden than spousal caregivers despite spending less time caring. Worse patient functional ability and more caregiver distress were independently associated with a greater burden in both adult-child and spousal caregivers. Additional factors were differentially associated with a greater caregiver burden in both groups. In adult-child caregivers these were: living with the patient, patient living in an urban location, and patient with a fall in the past 3 months; in spouses the factors were: caregiver gender (female) and age (younger), and more years of patient education. Conclusion: The perceived burden differed between adult-child and spousal caregivers, and specific patient and caregiver factors were differentially associated with this burden.